Interações e funções ecológicas desempenhadas por Scarabaeinae (Coleoptera: Scarabaeidae) e térmitas (isoptera) em áreas de pastagem e fragmentos de Mata Atlãntica no sul de Minas Gerais, Brasil - Alves, Frederico Resende (2015)
Dung beetles and termites are insects of great ecological importance due to the environmental services that they provide. Habitat fragmentation has a negative effect on both insect groups but some species can benefit by increasing their abundance. Even in degraded habitats, these insects continue to perform their environmental services, but not as efficient as occur in preserved areas. This study aimed to analyze the effect of habitat fragmentation on the diversity and feces removal of facultative coprophagous termites and dung beetles. The study was conducted in two different land use systems located in Alfenas-MG, southeastern Brazil: forest fragments of Atlantic rain forest and pastures. Dung beetles were collected by using pitfall traps and termites were captured directly from excrement plates. Feces removal was evaluated in artificial arenas (beetles) and with traps (termites) with different mesh openings. The results showed that dung beetles were more abundant during the rainy season. Additionally, the removal of feces was higher in the forest fragments during this season. On the other hand, termites removed more feces in the pastures during the dry season. Termites showed preference for dried feces whereas beetles were observed exploiting humid feces since they feed on the liquid rich in nutrients and microorganisms. The results suggest a tradeoff between food preference and removal of feces through the seasons leading to an indirect competition among these insects. When the loss of water becomes more pronounced, the dung beetles leave fecal masses which are then exploited by the termites. This effect is more pronounced in the pastures during the dry season. In this context, termites were more efficient in feces removal in degraded areas were the diversity of dung beetles is low.